PENGARUH KEBIJAKAN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI DAN FOOD AND BEVERAGE DI BEI - Wayudi, Arya Darma; Wiksuana, I Gusti Bagus; Sedana, Ida Bagus Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study is to analyze and compare cash turnover, accounts receivable turnover, inventory turnover, and turnover of working capital on profitability (earning power) in the pharmaceutical and food and beverage. Secondary data from the financial statements of the pharmaceutical companies and food and beverage with the time period 2011 - 2014 in this study. Purposive sampling method for sample collection technique as many as 19 of the 35 companies listed on the Indonesia Stock Exchange. This study using multiple linear regression analysis, t test, and F test. The results showed that the turnover of cash; accounts receivable turnover; inventory turnover; and working capital turnover simultaneous effect on profitability in pharmaceutical and food and beverage company found is different result. Cash turnover is significant negative effect on the profitability of the pharmaceutical and food and beverage. Accounts receivable turnover, inventory turnover, and turnover of working capital partially weren’t significant effect on the profitability of the pharmaceutical and food and beverage.